Compositional analysis and origin of the Peñas Coloradas Formation, Río Chico Group (Late Paleocene-Eocene?), in the eastern region of the Golfo de San Jorge basin, Chubut, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This work describes the sandstone composition and provenance of the Peñas Coloradas Formation (Late Paleocene-Eocene?) located in the eastern sector of the Golfo de San Jorge basin, in the Chubut Province. Sandy sections in the unit from the profiles of the localities of Punta Peligro, Estancia La Rosa and Cañadón Hondo (Fig. 1) were analyzed petrographically, together with the diffractometric analysis of sandy and shale levels. The obtained data were used to define detritic modes, classify sandstones, differentiate petrofacies, and to infer the possible source of materials, in a warm and humid paleoclimatic context.In this part of the basin, the Peñas Coloradas Formation is composed of thin bedded conglomerates and sandstones of variable grain sizes (fine to coarse) with intercalated mudstone beds, which show evidences of pedogenesis. They are composed by grey to reddish epiclastic and volcaniclastics, with an average thickness of 80 m and representing a fluvial system of high to moderate energy (Fig. 2). The paleontological record is represented by fossil woods suggesting a warm and humid weather (Brea et al., 2004, Brea and Zucol, 2006 and Raigemborn et al., 2006) and mammals remnants of Late Paleocene age belonging to the Carodnia Fauna (Simpson, 1935).The Golfo San Jorge extensional basin was developed during the Jurassic and Cretaceous in a cratonic setting (Hechem and Strelkov, 2002). An extensive marine flooding took place from Maastrichtian to Early Paleocene, when the Salamanca Formation was deposited (Uliana and Legarreta, 1999). During the late Paleocene, the sedimentation evolved into a continental environment with the deposition of the Río Chico Group: Peñas Coloradas, Las Flores and Koluél Kaike formations was characterized by recurrence of lacustrine and fluvial conditions (Legarreta and Uliana, 1994). Contemporarily, a bimodal calcoalcaline volcanism developed in the Pilcaniyeu Belt (Rapela and Kay, 1988).Medium to coarse sandstones with matrix < 15 % was used in order to analyze provenance using the Gazzi-Dickinson method (Ingersoll et al., 1984; Zuffa, 1985). At least 300 clasts were counted per thin section. The recognized components are shown in Table 1. The average composition of the plagioclases isandesine-oligoclase and that of the K-feldspar is sanidine and microcline. Scarce volcanic lithics show dissolution (Figure 3c), developing a pseudomatrix (Dickinson, 1970). Clay and siliceous cements are abundant in many sandstone samples (Figure 3a and b). Less commonly, cementation is by iron oxide and calcite. Sandstones from Peñas Coloradas Formation are not intensely altered diagenetically.The classification diagram of Folk et al. (1970) shows an average Q21F43L36 (Fig. 4 and Table 2). In general, the analyzed samples present a predominance of plagioclase over K-feldspar and relationships of Lv/L close to 1. These sandstones show increased proportions of quartz and feldspar, and decreases in the relative proportion of lithics with time.Two petrofacies were differentiated (Table 2). The petrofacies I (Q28 %) is integrated by lithic feldarenites (Q36F40L24), showing a P/K relation smaller than in petrofacies I with more abundant feldspar than in lithic fragments (Fig. 3a and c). This petrofacies is observed in the upper sections of the Peñas Coloradas Formation.The X-Ray analysis (Table 3) was carried out in air-dried, glycolated and heated samples (550º C) over samples coming from shales (< 4 ìm fraction). Semi-quantitative estimations of contents of identified species were performed by measuring peak areas on glycolate preparations (Biscaye, 1965). The smectite is the most abundant clay mineral, with kaolinite, illite and interestratificated I/S. Clinoptilolite and amorphous silica (opal-CT) are present in all of the samples. This mineralogical association can be attributed to the alteration of ash (De Ros et al., 1997) under warm and humid climatic conditions, with certain seasonality (Dingle and Lavelle, 2000).Cross-bedding and orient trunks of the Peñas Coloradas Formation indicate a uniform axial sedimentary transport from NW and W to SE and W (Fig. 2). The provenance area is viewed in the diagrams QtFL (Fig. 4b) and QmFLt (Fig. 4c) (Dickinson and Suczek, 1979; Dickinson et al., 1983). The samples show magmatic arc provenance from transitional arc (petrofacies I) to dissected arc (petrofacies II), and they show increased proportions of quartz and feldspar. This compositional change may record the arc dissection (Dickinson et al., 1983), being the volcanic cover removed gradually, leading to the partial exposition of the batholithic rocks of the arc, during the latest stages.The characteristics of the petrofacies I indicate a supply from the volcanic cover of the magmatic arc (Valloni and Mezzadri, 1984). The petrofacies II displacement is related to the gradual removal of the volcanic cover and the partial exposition of the arc granitic roots (Marsaglia and Ingersoll, 1992). The absence of plutonic origin fragments could also be due to the fact that these are separate in their individual mineral components in the analyzed sandy fraction. At the same time, the partial dissolution and alteration observed in the majority of potassic feldspar grains may be attributed to their low chemical stability under humid and warm weather (Suttner et al., 1981). It is interesting to note that the proportion of K-feldspar in the QmPK diagram (Fig. 4d) does not vary significantly, indicating that the arc provenance was not exhumed deeply enough to expose its plutonic root (Yan et al., 2006).Petrography data from Peñas Coloradas Formation suggest that they were derived mainly form a magmatic arc, where the sedimentary-volcanic cover was removed gradually, leading to the partial exposition of the batholithic rocks during the latest stages. Paleocurrent indicators demonstrate that this arc was located in the west and northwest of the study area.Given the compositional characteristics of the Peñas Coloradas Formation and the important volcanic activity during the Paleocene in Patagonia, it may be deduced that the main part of the materials have been provided from the Paleocene-Eocene arc of Pilcaniyeu Belt (Rapela and Kay, 1988), situated to the northwest of the study area (Raigemborn, 2005). The latter was developed between 60 and 43 Ma in northern Patagonian (40 to 43ºS), represented by a bimodal calcoalcaline volcanism composed of basaltic to rhyolitic rocks with ignimbritic facies (Rapela et al., 1984), under a warm and humid but seasonal climate (Aragón and Romero, 1984).A minor contribution from Paleocene Plateau Basalt and older volcanic units is not ruled out, such as the Middle Jurassic of the Marifil Complex and Cretaceous of the Divisadero Group or equivalents, which crop out towards the W and NW of the study area.
Keywords: Detritic modes; Petrofacies; Provenance; Peñas Coloradas Formation; Golfo de San Jorge Basin